STUDENTS’ DAYLIGHT CONDITION PERCEPTION IN TASMI’ CLASSROOM - Fadli, Arabi; Elina, Mohd Husini; Raja Nur Syaheeza, Raja Mohd Yazit (2020)
A renewable energy source that is important for human daily task performance is daylighting according to photobiologist. These daily task requires visual comfort for optimal performance such as writing and reading. These tasks are also commonly performed as educational process in learning spaces such as classrooms. Various research shows that the improvement of students’ performance can be highly influenced by the improvement of daylighting as well. Learning spaces requires illuminance level between 300lux to 500lux based on recommendations in various standards and guidelines. Recent increment of more than 900 religious school establishment shows that the demand for Ulul Albab education among Malaysians increases since 2011. Tasmi’ is one of the method used for Quran ‘hafazan’ (memorization) learning process as a part of Ulul Albab education. Kolej Permata Insan has adapted the Tasmi’ method in their Ulul Albab education and as far as designing a Tasmi’ classroom specifically for Quran ‘hafazan’ teaching. However, since the learning process follows a tradition of using a book rest or ‘rehal’, the illuminance level required for visual comfort and optimum learning task performance in the Tasmi’ classrooms differs. The main focus of this research is to evaluate the students’ perceptions on the daylight condition in the Tasmi’ classrooms through data collected from the provided questionnaire. Results shows that all of the classrooms exceeds the recommended illuminance level. Thus, this reduces the students’ visual comfort based on the result of the questionnaire on the students’ perception. Further study for Tasmi’ acceptable illuminance level is required.